Theological Discourse in the Formation of the Literary Tale: How Worldview came to Dominate Narrative - Aliona Matiychak; Olha Chervinska; Natalia Nikoriak; Tetiana Basniak; Alyona Tychinina (Interlitteraria, 2022)
This study is motivated by new perspectives that help to expend the boundaries of multidisciplinary research. The article examines the discourse on the literary tale with regard to its theological specificity of narrative and how worldview came to dominate it. The most significant examples of German, Russian, Polish, Romanian and Ukrainian tales are analysed, taking into consideration national ethos. The specifics of the genre are explored in their historical and cultural contexts, with an emphasis on the difference between the literary tale and the folktale. Previous research indicates that the poetics of literary tales of this type has not been studied sufficiently. The paper aims to examine the literary tale within an ethno-national historical context, considering the main aspects of the Christian religious ethos of the 19th century. Our methodology includes an integrative multidisciplinary approach that combines the principles of historical poetics, hermeneutics, receptive poetics and classical methods of folkloristics in the light of transitivity theory.